Положення 1892 р.: вплив губернатора та Губернського із земських і міських справ присутствія на процес формування й діяльність міського громадського управління - Шара, Л. (Сiверянський лiтопис, 2015)
Йдеться про вплив очільника коронної адміністрації та Губернського із земських і
міських справ присутствія на процес формування й діяльність органів міського самоврядування відповідно до Положення 1892 р. Наголошується на контролюючих функціях
стосовно поточної роботи громадського управління, можливостях притягнення до відповідальності його службовців. Водночас, указується на право самоврядних структур опротестовувати рішення губернатора та Губернського із земських і міських справ присутствія у Сенаті. Речь идёт о влиянии главы коронной администрации и Губернского по земским и городским делам присутствия на процесс формирования и деятельность органов городского
самоуправления в соответствии с Положением 1892 г. Подчёркиваются контролирующие функции относительно текущей работы общественного управления, возможности привлечения к ответственности его служащих. В тоже время указывается на право
самоуправных структур опротестовывать решения губернатора и Губернского по
земским и городским делам присутствия в Сенате. The Office essentially acted the role of arbitrator between the public government, on the
one hand, and the governor and the local community – on the other hand. It was foreseen the
principle of making collective decisions by members of the Office and involving Mayor and
elected member of the duma to it will impartially resolve issues important for the local government
. If the last one still had doubts about the objectivity of the Office decision or disagreed with it,
the law provided the right to defend your position by appealing to the Minister of the Interior
or the Senate. For a comprehensive assessment the possibilities of the provincial governor and
Provincial office of zemstvo and city affairs to influence on the activity of public governance
reasonably to reconstruct the Provision of 1892 in practice, that requires a separate special study.